Aleksandr Vasilyevich Demchenko - Staff of SI «SISJP NAMS», - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the memory of O. Demchenko - an amazing person, a talented orthopedist traumatologist, scientist, wonderful surgeon and mentor.